MRI free water as a biomarker for cognitive performance: Validation in the MarkVCID consortium. Issue 1 (13th December 2022) - Maillard, Pauline; Hillmer, Laura J.; Lu, Hanzhang; Arfanakis, Konstantinos; Gold, Brian T.; Bauer, Christopher E.; Kramer, Joel H.; Staffaroni, Adam M.; Stables, Lara; Wang, Danny J.J.; Seshadri, Sudha; Satizabal, Claudia L.; et al.
Abstract : Introduction: To evaluate the clinical validity of free water (FW), a diffusion tensor imaging–based biomarker kit proposed by the MarkVCID consortium, by investigating the association between mean FW (mFW) and executive function. Methods: Baseline mFW was related to a baseline composite measure of executive function (EFC), adjusting for relevant covariates, in three MarkVCID sub‐cohorts, and replicated in five, large, independent legacy cohorts. In addition, we tested whether baseline mFW predicted accelerated EFC score decline (mean follow‐up time: 1.29 years). Results: Higher mFW was found to be associated with lower EFC scores in MarkVCID legacy and sub‐cohorts ( p ‐values < 0.05). In addition, higher baseline mFW was associated significantly with accelerated decline in EFC scores ( p = 0.0026). Discussion: mFW is a sensitive biomarker of cognitive decline, providing a strong clinical rational for its use as a marker of white matter (WM) injury in multi‐site observational studies and clinical trials of vascular cognitive impairment and dementia (VCID).